2022
DOI: 10.1002/ajim.23344
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related allergy and asthma associated with cleaning agents in health workers in Southern African tertiary hospitals

Abstract: Background: Health workers (HWs) are exposed to diverse cleaning agents in large hospitals. This study determined the prevalence of work-related symptoms, allergic sensitization, and lung function abnormalities in HWs of two tertiary hospitals in Southern Africa. Methods: A cross-sectional study of 699 HWs (South Africa: SAH, n = 346; Tanzania: TAH, n = 353) was conducted. Health outcomes were assessed using a standardized ECRHS questionnaire, immunological tests (specific IgE antibody to common aeroallergens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 68 publications
(156 reference statements)
2
12
0
Order By: Relevance
“…The prevalence of symptoms (ranging from 8% to 22%) was similar to that reported by other studies, but current asthma (7.8%) in our sample was at the lower end of the ranges reported in the literature, with studies reporting prevalence from 11% (Spanish and Brazilian cleaners) through to 22.4% among New Zealand cleaners, but similar to reported findings among South African healthcare workers (6%) 8,10,14,22,27,28 . This lower asthma prevalence among three separate cohorts in Southern Africa, compared to the reporting of asthma‐like symptoms within our sample could be an indication of under‐diagnosis and lack of access to health services.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The prevalence of symptoms (ranging from 8% to 22%) was similar to that reported by other studies, but current asthma (7.8%) in our sample was at the lower end of the ranges reported in the literature, with studies reporting prevalence from 11% (Spanish and Brazilian cleaners) through to 22.4% among New Zealand cleaners, but similar to reported findings among South African healthcare workers (6%) 8,10,14,22,27,28 . This lower asthma prevalence among three separate cohorts in Southern Africa, compared to the reporting of asthma‐like symptoms within our sample could be an indication of under‐diagnosis and lack of access to health services.…”
Section: Discussionsupporting
confidence: 90%
“…A retrospective case series analyses found that cleaning products that induce a reduced FEV1 response contained sensitising QACs 13 . Chloramines and orthophthalaldehydes are other sensitizers found in cleaning agents and with sensitisation reported among cleaners 14 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations